Growth Response of Cocoa Seedlings (Theobroma cacao L.) to Concentration and Application Interval of Forest Organic Fertilizer - Novi Mailidarni; Jauhari Jauhari (Postgraduate, University of Mataram, 2026)
Vegetation plays an essential role in regulating soil fertility through nutrient cycling, organic matter accumulation, and interactions with soil microorganisms. This study aimed to evaluate the chemical characteristics and soil fertility status under vegetation dominated by Mimosa invisa L., Crotalaria anagyroides L., and Imperata cylindrica L. Beauv. in Baitussalam District, Aceh Besar Regency, Indonesia. Soil samples were collected from the 0–20 cm layer using a non-factorial randomized block design with five replications. Soil chemical analyses included pH, organic carbon, total nitrogen, available phosphorus, exchangeable potassium, calcium, magnesium, sodium, cation exchange capacity (CEC), exchangeable sodium percentage (ESP), and exchangeable hydrogen. Data were analyzed using analysis of variance (ANOVA), followed by the Least Significant Difference (LSD) test at the 5% significance level. The results showed that vegetation type significantly affected available phosphorus and exchangeable calcium but had no significant effects on soil pH, total nitrogen, exchangeable potassium, magnesium, sodium, CEC, ESP, or exchangeable hydrogen. Soils under Mimosa invisa generally exhibited higher soil pH, organic carbon, total nitrogen, CEC, and exchangeable calcium than those under Crotalaria anagyroides and Imperata cylindrica. High exchangeable sodium and ESP values across all vegetation types indicated persistent effects of seawater intrusion following the 2004 Indian Ocean tsunami. These findings demonstrate that vegetation type influences nutrient cycling and selected soil chemical properties, with leguminous vegetation showing greater potential to improve soil fertility. The study provides valuable information for developing sustainable soil management and ecological restoration strategies in tropical coastal ecosystems.